THE ROLE OF TEACHERS IN CREATING A JOYFUL LEARNING ATMOSPHERE THROUGH INTERACTIVE ACTIVITIES IN GRADE 2 OF MUHAMMADIYAH 1 ELEMENTARY SCHOOL, SURAKARTA - Mayva Retno Wulandari; Harun Joko Prayitno (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to describe the contribution of teachers in creating a pleasant learning environment by implementing Joyful Learning based on interactive activities for second-grade students at Muhammadiyah 1 Elementary School in Surakarta. The method used in this study is a descriptive qualitative approach with a case study design. Information was collected through interviews with teachers and students, observations of the learning process, and collection of documentation of teaching and learning activities. The findings of this study indicate that the contribution of teachers in creating a pleasant learning environment is realized through several key aspects, namely teachers as designers of interactive learning, as facilitators of learning activities, as supportive class managers, and as motivators who provide positive reinforcement to students. These roles are realized through the use of educational games, group discussions, questions and answers, ice breakers, and the use of visual media and concrete materials that are appropriate to the characteristics of lower-grade students. The implementation of this teacher role can improve learning concentration, active participation, cooperation between students, as well as motivation and emotional involvement of students in a positive way during the learning process. Therefore, Joyful Learning through interactive activities has proven effective in creating a conducive and meaningful learning climate and supporting the cognitive, social, and emotional development of students in elementary schools